The Utilization of Voluntary Counseling and Testing by Women of Reproductive Age in West Papua (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Women of reproductive age living with the human immunodeficiency virus (WRALHIV) have many complex problems regarding their disease and status. They have to access Voluntary counseling and testing (VCT) as one of the health services where they would receive antiretroviral treatment to optimize their health and improve their quality of life. The study aims to analyze the factors which determine the utilization of VCT for accessing antiretroviral treatment by WRALHIV in West Papua. It was an observational, cross-sectional study. The subject was women of reproductive age (WRA) aged 15-49 years old, receiving antiretroviral treatment at VCT of Hospitals in Manokwari, Sorong, and Fakfak. The total was 140 respondents. Data collection was carried out by interviews using a questionnaire. The data were analyzed statistically using the chi-square and logistic regression tests. Most respondents with high intensity in the utilization of VCT services were aged 15-35 years, graduated from senior high school - university, unemployed, and married. Demographic and predisposing variables were not significantly associated, but there were significant associations between enabling factors (distance) with p value=0.00 and reinforcing factor (social support) with p value=0.03 in the utilization of VCT services by WRALHIV in West Papua, in which the distance was more significant than social support in the utilization of VCT services. The easily accessible distance increases their visitation to VCT. In addition, social support had an impact on increasing the utilization of VCT services, and finally, these may improve WRALHIV quality of life.